2023
DOI: 10.1109/tsmc.2023.3282141
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate Variability Measurement to Assess Acute Work-Content-Related Stress of Workers in Industrial Manufacturing Environment—A Systematic Scoping Review

Abstract: Background: Human workers are indispensable in the human-cyber-physical system in the forthcoming Industry 5.0. As inappropriate work content induces stress and harmful effects on human performance, engineering applications search for a physiological indicator for monitoring the well-being state of workers during work; thus, the work content can be modified accordingly. The primary aim of this study is to assess whether heart rate variability (HRV) can be a valid and reliable indicator of acute work-content-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…The scientific validity of stress detection through HRV assessment is substantiated by neurobiological evidence [43]. Nevertheless, Tran et al [44] suggested that HRV does not fully reflect the work-content-related stress during work, and it is problematic to measure the effect of work-content-related stress on HRV in the real manufacturing environment. Tran et al [44] stated that since HRV strongly depends on too many factors (e.g., work context, individual physical and mental status), its real-time usage for stress monitoring can be problematic.…”
Section: Work-related Stress Measurement In the Industrial Contextmentioning
confidence: 99%
See 2 more Smart Citations
“…The scientific validity of stress detection through HRV assessment is substantiated by neurobiological evidence [43]. Nevertheless, Tran et al [44] suggested that HRV does not fully reflect the work-content-related stress during work, and it is problematic to measure the effect of work-content-related stress on HRV in the real manufacturing environment. Tran et al [44] stated that since HRV strongly depends on too many factors (e.g., work context, individual physical and mental status), its real-time usage for stress monitoring can be problematic.…”
Section: Work-related Stress Measurement In the Industrial Contextmentioning
confidence: 99%
“…Nevertheless, Tran et al [44] suggested that HRV does not fully reflect the work-content-related stress during work, and it is problematic to measure the effect of work-content-related stress on HRV in the real manufacturing environment. Tran et al [44] stated that since HRV strongly depends on too many factors (e.g., work context, individual physical and mental status), its real-time usage for stress monitoring can be problematic. They emphasized the need for more comprehensive studies to distinguish work-related stress from typical stress types, as existing studies lacked solid scientific conclusions about the relationship between work-related stress and HRV [44].…”
Section: Work-related Stress Measurement In the Industrial Contextmentioning
confidence: 99%
See 1 more Smart Citation